Pemanfaatan Aplikasi Digital sebagai Instrumen Evaluasi Pembelajaran di Satuan PAUD: Efisiensi, Objektivitas, dan Tantangannya - Ade Irma; Kesya Syakirah Putri; Zakya Nesa Prastiti; Dwi Nomi Pura (Early Childhood Research and Practice, 2026)
Learning evaluation in Early Childhood Education (PAUD) is often hampered by the burden of manual administration that consumes educators' time. This article aims to analyze the use of digital applications to transform the assessment process from a conventional one to a more dynamic and integrated one. The method used is a literature review with a qualitative descriptive approach. The results of the discussion indicate that the use of digital platforms can increase the efficiency of documenting child development achievements in real time, strengthen data validity through multimedia evidence, and facilitate communication and reporting to parents. However, its implementation still faces challenges in the form of gaps in teacher digital literacy and limited infrastructure. The conclusion of this article emphasizes that digitalization of evaluation is not intended to replace the role of teachers, but rather as a tool to improve the quality of interactions and the objectivity of child development assessments.